Aturan Kewajiban Pembagian Tirkah Menurut Konsep Fiqih Prioritas atau Fiqh Al-Awlawiyyat - Lutfia Rahmawati (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Fiqh al-awlawiyyat is a discipline that focuses on placing an entity in its rightful position through the application of comprehensive standards known as dhawabith al-awlawiyyat. These standards are assessed through various aspects such as the level of benefit, efforts to avoid harm, and the efficiency of their implementation. This article is the result of literature research applying a normative juridical approach. The method used is descriptive analysis with primary sources in the form of literature on fiqh al-awlawiyyat. Additionally, secondary sources include literature on fiqh and ushul al-fiqh relevant to the research variables. The research findings indicate that the distribution of tirkah obligations involves several aspects, including the obligation to distribute joint ownership rights, the obligation to distribute funeral management costs, the obligation to distribute deceased debts settlement costs, the obligation to distribute wills, and the obligation to distribute inheritance assets.